2013
DOI: 10.1590/s0100-736x2013000200004
|View full text |Cite
|
Sign up to set email alerts
|

Causas de aborto bovino diagnosticadas no Setor de Patologia Veterinária da UFRGS de 2003 a 2011

Abstract: Descrevem-se as causas de aborto bovino diagnosticadas no Setor de Patologia Veterinária da Universidade Federal do Rio Grande do Sul no período de janeiro de 2003 a dezembro de 2011. Um total de 490 fetos bovinos foi analisado neste período. Causas específicas de aborto foram encontradas em 46,7% dos casos. Infecções por protozoários, em especial Neospora caninum acometeram 33% dos casos (162/490). Bactérias com 6,3% (31/490), seguidas por fungos com 0,8% (4/490) dos casos, foram causas adicionais de abortos.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0
8

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 27 publications
2
20
0
8
Order By: Relevance
“…Pregnancy loss rates have proved lower when cows are vaccinated at least 30 days before FTAI, with a second dose at D0 (Aono et al 2013, Pereira et al 2013. In lactating beef cows, however, FTAI is typically started 30-45 days post-calving, requiring the initial vaccine dose to be administered in late pregnancy (potentially resulting in miscarriage) or shortly after parturition (with a risk of newborn death as a result of handling) (Antoniassi et al 2013). Experiment 2 of the present study revealed the feasibility of using two vaccination protocols -namely, VACGEST (vaccination on D0 and at 30 DPI) and VACPREV (vaccination on D0 and D11), which facilitates vaccination planning.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pregnancy loss rates have proved lower when cows are vaccinated at least 30 days before FTAI, with a second dose at D0 (Aono et al 2013, Pereira et al 2013. In lactating beef cows, however, FTAI is typically started 30-45 days post-calving, requiring the initial vaccine dose to be administered in late pregnancy (potentially resulting in miscarriage) or shortly after parturition (with a risk of newborn death as a result of handling) (Antoniassi et al 2013). Experiment 2 of the present study revealed the feasibility of using two vaccination protocols -namely, VACGEST (vaccination on D0 and at 30 DPI) and VACPREV (vaccination on D0 and D11), which facilitates vaccination planning.…”
Section: Discussionmentioning
confidence: 99%
“…In most cases, the causes of these losses remain undetermined (Corbellini et al 2006, Antoniassi et al 2013). There are no conclusive studies on the efficiency of vaccination against IBR/BVDV/Leptospirosis in the prevention of reproductive losses caused by these diseases in cattle.…”
Section: Introductionmentioning
confidence: 99%
“…Estas são amplamente estudadas, porém dentre esses distúrbios também são descritas afecções causados por plantas e outras toxinas. O desconhecimento da maioria dos seus mecanismos patogenéticos, faz com que sua importância não seja completamente reconhecida (James et al 1992, Lucena et al 2010, Riet-Correa et al 2012, Caldas et al 2011, Antoniassi et al 2013. Dessa forma, ainda se faz necessário o estudo detalhado das possíveis alterações reprodutivas causadas por princípios tóxicos de plantas e esse trabalho vem contribuir para o entendimento dessas interações.…”
Section: Discussionunclassified
“…Nos rebanhos bovinos brasileiros, a diversidade de condições de manejo, a falta de suporte laboratorial e o envio de fetos em autólise para necropsia dificultam o diagnóstico da etiologia do aborto, de maneira que faltam ainda muitas informações sobre as causas de aborto em bovinos no Brasil (Antoniassi et al 2013). Entre as diversas etiologias do aborto, destacam-se as de origem infecciosa, com abortos causados por protozoários, bactérias, vírus e fungos.…”
Section: Introductionunclassified
“…Abortos bacterianos são associados a Brucela abortus, Leptospira sp., Listeria monocytogenes e Campylobacter sp. (Varaschin & Wouters 2006, Alves et al 2011); já os de origem viral são relacionados ao Vírus da Diarreia Viral Bovina (VDVB) e ao Herpesvírus Bovino tipo I (HVB-1) (Varaschin & Wouters 2006, Antoniassi et al 2013.…”
Section: Introductionunclassified